Detection of RR interval alterations in ECG signals by using first order fractional filter - Alagoz, Baris Baykant; Yeroglu, Celaleddin; Kavuran, Gurkan; Ates, Abdullah (Institute of Electrical and Electronics Engineers Inc., 2016)
Sleep apnea syndrome deteriorates sleeping quality and daily performance of many individuals. This study presents utilization of fractional-order low pass filtering for the detection of RR interval alteration from electrocardiogram (ECG) signals. In the case of sleeping apnea, cardiac interbeat intervals prolong and it is viewed as an indication of obstructive sleep apnea state. The prolonged interbeat intervals manifest themselves as the decrease of R peak frequency (increase of RR intervals) in ECG signals. It results in shifting of spectral components composing R peaks towards lower frequencies in energy signal of ECG. In order to detect prolonging interbeat intervals, energy signal calculated from ECG is applied to low-pass fractional-order filter. Transition band of the low-pass filter is used as a ramp filter in order to detect frequency variations in the energy of R peaks. We compare results of the first order fractional-order and integer order low-pass filters and demonstrate that the fractional-order filter can improve the detection performance of low-pass filtering by modifying transition band slope of low-pass filters. © 2016 IEEE.
39th International Conference on Telecommunications and Signal Processing, TSP 2016 -- 27 June 2016 through 29 June 2016 -- Vienna -- 125124
Keywords: Apnea detection; ECG; Fractional-order system; Low-pass filter